About-Weekly Pattern in the Dynamic Complexity of a Healthy Subject’s Cellular Immune Activity: A Biopsychosocial Analysis - Seizer, Lennart; Cornélissen-Guillaume, Germaine; Schiepek, Günter; Chamson, Emil; Bliem, Harald R.; Schubert, Christian (Frontiers in Psychiatry, 2022)
In a previous integrative single-case study, we collected biological, psychological and social time-series data on a 25-year-old healthy woman over the course of 126 12-h intervals (63 days) and used urinary neopterin as an indicator of cellular immune activity [Schubert et al. 2012 (1)]. The present re-evaluation introduced Dynamic Complexity (DC) as an additional non-linear and non-stationary measure to further investigate the subject’s biopsychosocial dynamics during the study. The new time series dealing with urinary neopterin complexity revealed a cyclic, circaseptan (about-weekly) repeating pattern (6.59 days). The only weekly reoccurring events over the course of the study that were associated with this immunological pattern were the in-depth interviews with the subject (mean distance between interviews: 6.5 days). Superposed epoch analysis (SEA) revealed a U-shaped relation between neopterin complexity and interviews, with a decrease in neopterin complexity before and during interviews and an increase after interviews. Furthermore, the complexity scores for irritation, anxiousness/depressiveness and mental activity were positively correlated with neopterin complexity. The results suggest that the interviews, which had been found to be related to the subject’s need for educational and/or social accomplishment, were marked by stress (decrease in psycho-immunological flexibility and adaptability), which was then relieved after the interviews (increase in psycho-immunological flexibility and adaptability). It appears that the subject’s cellular immune activity, as indicated by neopterin complexity, functionally mirrored the emotional meaning she ascribed to the in-depth interviews. This re-evaluation is in line with the view that biopsychosocial research requires multimodal analysis of single cases based on qualitative (e.g., in-depth interviews) and quantitative (e.g., time series analysis) data under conditions of “life as it is lived

Ambulatory Assessment in Mental Health Research: Expert Consensus on Current Practices and Future Directions - Löchner, Johanna; Santangelo, Philip Samuel; Ansell, Emily; Bolger, Niall; Ebner-Priemer, Ulrich; Fried, Elko; Gawrilow, Caterina; Hamaker, Ellen; Hepp-Kieslich, Johanna; Kaurin, Aleksandra; Kirtley, Olivia J; Kubiak, Thomas; et al. (2025)
Ambulatory Assessment (AA) studies have proliferated in mental health science,promising unparalleled insights into the dynamic nature of mental health. Thehigh methodological heterogeneity of AA studies calls for the harmonization ofapproaches and the establishment of research standards. This expert consensusprovides an overview of best-practice recommendations to integrate AA in mentalhealth research. We queried 26 experts in the field in a Delphi-adapted process,resulting in recommendations regarding eight topics, encompassing method-ological considerations, technological advancements, and practical applications;interdisciplinary collaboration and personalized treatment approaches were recur-rent themes. By establishing standardized guidelines and best practices, thisexpert consensus serves as a resource for mental health scholars seeking to lever-age AA tools in research and practice. Ultimately, the integration of AA holdspromise for revolutionizing mental health care, fostering precision medicine, andimproving outcomes for individuals living with mental disorder
https://cris.fau.de/converis/publicweb/Publication/336310725
Keywords: Ambulatory Assessment; Ecological Momentary Assessment; ExperienceSampling Method; Guidelines; Delphi Method; Mental Health

Anticipated stress predicts the cortisol awakening response: An intensive longitudinal pilot study - Seizer, Lennart (Biological Psychology, 2024)
The cortisol awakening response (CAR) has been hypothesized to prepare the body for anticipated demands of the upcoming day. This pilot study investigates the influence of anticipated stress on the upcoming day on the CAR, using an intensive longitudinal design with ecological momentary assessments. Over a 30-day period, three healthy participants collected saliva samples each morning at three time points after awakening to measure cortisol levels and completed a questionnaire each evening on the anticipated stress for the following day. Additionally, they wore a smart headband to objectively determine the time point of awakening. There was high variability in the CAR magnitude within participants over time. A multi-level model was estimated to investigate the influence of anticipated stress on the CAR. Results indicated that anticipated stress is predictive of the CAR on the following morning, with higher anticipated stress being associated with increased cortisol levels at the post-awakening time points. These findings underscore the role of stress anticipation in modulating the CAR and highlight the importance of considering within-person variation and temporally lagged effects in biopsychological research.
Created from Fastlane, Scopus look-up
Keywords: Ambulatory assessment; Anticipation; Cortisol awakening response; Intensive longitudinal data; Stress

A Primer on Sampling Rates of Ambulatory Assessments - Seizer, Lennart; Schiepek, Günter; Cornélissen-Guillaume, Germaine; Löchner, Johanna (Psychological Methods, 2024)
The use of ambulatory assessments (AAs) as an approach to gather self-reported questionnaires or selfcollected biochemical data is constantly increasing to investigate the experiences, states, and behaviors of individuals and their interaction with external situational factors during everyday life. It is often implicitly assumed that data from different sampling protocols can be used interchangeably, despite them assessing processes over different timescales in different intervals and at different occasions, which depending on the variables under study may result in fundamentally different dynamics. There are multiple temporal parameters to consider and while there is an abundance of sampling protocols that are applied regularly, to date, there is only limited empirical background on the influence different approaches may have on the data and findings. In this review, we aim to give an overview of commonly used types of AA in psychology, psychiatry, and biobehavioral research with a breakdown by temporal design parameters. Additionally, we discuss potential advantages and pitfalls associated with the various approaches.
CRIS-Team Scopus Importer:2024-11-26
Keywords: ambulatory assessment; ecological momentary assessment; experience sampling method; intensive longitudinal data; time series

Bridging acute and chronic stress effects on inflammation: protocol for a mixed-methods intensive longitudinal study - Seizer, Lennart; Pascher, Anja; Branz, Sonja; Schmitt, Nadine; Löchner, Johanna; Schuller, Björn W.; Rohleder, Nicolas; Renner, Tobias J. (BMC Psychology, 2025)
Acute stress triggers adaptive physiological responses—including transient increases in inflammatory cytokines—while chronic stress is associated with sustained inflammatory activity that may underlie the development of various disorders. Despite extensive research on each stress type individually, the transition and interaction between them remain underexplored. This study aims to address this gap by employing an intensive longitudinal measurement burst design. Healthy university students will be recruited and monitored over three one-week assessment bursts, spaced by three-month breaks. Participants will complete ecological momentary assessments four times daily, recording their emotional states, stress experiences, and daily incidents. Simultaneously, saliva samples will be collected at matching time points to measure biomarkers of immune and stress system activity. In addition, daily audio diaries will provide qualitative context through advanced speech analysis techniques. Data will be analyzed using a multi-level modeling approach to differentiate within-person dynamics from between-person variability, accounting for potential moderators. The findings are expected to shed light on how repeated acute stressors transition into chronic stress and how chronic stress burden may influence acute stress responses.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Ecologcial momentary assessment; Inflammation; Intensive longitudinal data; Psychoneuroimmunology; Stress

Cognitive behavioral therapy for pediatric obsessive-compulsive disorder delivered via internet videoconferencing: a manualized sensor-assisted feasibility approach - Klein, Carolin S.; Alt, Annika K.; Pascher, Anja; Kühnhausen, Jan; Seizer, Lennart; Ilg, Winfried; Thierfelder, Annika; Primbs, Jonas; Menth, Michael; Barth, Gottfried M.; Gawrilow, Caterina; Conzelmann, Annette; et al. (Child and Adolescent Psychiatry and Mental Health, 2024)
Background: Between 1 and 4% of children and adolescents suffer from obsessive-compulsive disorder (OCD) worldwide, but the majority of these young people do not have access to cognitive behavioral therapy (CBT) as a first-line treatment. CBT delivered via online videoconferencing (vCBT) offers a new way to provide young people with therapy, especially in the home environment where symptoms usually occur. Methods: In this study, we investigated the feasibility of a newly revised vCBT manual, symptom change during treatment, and effects on family life and social functioning. 20 patients with OCD, aged 12–18 years, were treated during 14 weekly sessions while using a multimodal sensor system that assessed their physiological and behavioral responses during therapy. Treatment was delivered in real time via an online videoconferencing platform. Measurements of feasibility, acceptance, and implementation were evaluated descriptively, and clinical measures were assessed with t tests. Results: The primary results showed that patients and parents perceived the manual-based vCBT as feasible and easy to understand. According to the therapists’ ratings, all treatment modules and the content could be carried out in accordance with the manual. As a secondary outcome, OCD symptoms improved significantly during treatment (p <.001, d = 1.87), revealed by an average decrease of more than half in the Children’s Yale-Brown Obsessive-Compulsive Scale (CY-BOCS) score. As the psychotherapy could be implemented directly in the patients’ home environment, low barriers to participation were reported, and the majority of participants reported improvements in family life after treatment. Conclusions: In summary, the results of this feasibility study indicated a successful application of manual-based psychotherapy delivered via videoconferencing for pediatric OCD supported by a sensor system. This method should be further investigated in future randomized controlled trials with larger patient samples. Clinical trial registration: [www.ClinicalTrials.gov], identifier [NCT05291611], first submission: 2021-12-10.
Created from Fastlane, Scopus look-up
Keywords: Children and adolescents; Internet-based cognitive behavioral therapy; Manualized treatment; Obsessive-compulsive disorder; Sensor technology

Computational charisma—A brick by brick blueprint for building charismatic artificial intelligence - Schuller, Björn W.; Amiriparian, Shahin; Batliner, Anton; Gebhard, Alexander; Gerczuk, Maurice; Karas, Vincent; Kathan, Alexander; Seizer, Lennart; Löchner, Johanna (Frontiers in Computer Science, 2023)
Charisma is considered as one's ability to attract and potentially influence others. Clearly, there can be considerable interest from an artificial intelligence's (AI) perspective to provide it with such skill. Beyond, a plethora of use cases opens up for computational measurement of human charisma, such as for tutoring humans in the acquisition of charisma, mediating human-to-human conversation, or identifying charismatic individuals in big social data. While charisma is a subject of research in its own right, a number of models exist that base it on various “pillars,” that is, dimensions, often following the idea that charisma is given if someone could and would help others. Examples of such pillars, therefore, include influence (could help) and affability (would help) in scientific studies, or power (could help), presence, and warmth (both would help) as a popular concept. Modeling high levels in these dimensions, i. e., high influence and high affability, or high power, presence, and warmth for charismatic AI of the future, e. g., for humanoid robots or virtual agents, seems accomplishable. Beyond, also automatic measurement appears quite feasible with the recent advances in the related fields of Affective Computing and Social Signal Processing. Here, we therefore present a brick by brick blueprint for building machines that can appear charismatic, but also analyse the charisma of others. We first approach the topic very broadly and discuss how the foundation of charisma is defined from a psychological perspective. Throughout the manuscript, the building blocks (bricks) then become more specific and provide concrete groundwork for capturing charisma through artificial intelligence (AI). Following the introduction of the concept of charisma, we switch to charisma in spoken language as an exemplary modality that is essential for human-human and human-computer conversations. The computational perspective then deals with the recognition and generation of charismatic behavior by AI. This includes an overview of the state of play in the field and the aforementioned blueprint. We then list exemplary use cases of computational charismatic skills. The building blocks of application domains and ethics conclude the article.
CRIS-Team Scopus Importer:2024-11-26
Keywords: affective computing; AI; charisma; empathy; mimicry; social signal processing

Diurnal variation of 8-hydroxy-2’-deoxyguanosine in continuous time series of two breast cancer survivors - Geuter, Joschua; Seizer, Lennart; Cornélissen-Guillaume, Germaine; Engin, Ayse Basak; Fuchs, Dietmar; Schubert, Christian (2025)
8-hydroxy-2’deoxyguanosine (8-OHdG) is an oxidative product removed from DNA following radical oxygen species-induced damage. Being water-soluble, it can be measured non-invasively in the urine and has thus been established as a marker for ‘whole-body’ oxidative stress. Its validity and reliability as an oxidative stress marker in various chronic diseases and early carcinogenesis screening in clinical diagnosis and research are widely debated. To determine optimal measurement timing and duration, it is essential to establish the circadian profile of 8-OHdG under everyday life conditions and use reliable sampling methods. Here, we show the presence of day-night differences for 8-OHdG normalized by creatinine or urine volume in continuous time series of two breast cancer survivors who participated in integrative single-case studies and sampled their urine in 12-h-pooled collections over one month. These findings support the importance of appropriately considering the dynamic characteristics of stress indicators to reduce the risk of inconsistent or false results in clinical diagnostic
https://cris.fau.de/converis/publicweb/Publication/336135204

Emotional states predict cellular immune system activity under conditions of life as it is lived: A multivariate time-series analysis approach - Seizer, Lennart; Fuchs, Dietmar; Bliem, Harald R.; Schubert, Christian (PLoS ONE, 2023)
The relationship between emotional states and immune system activity is characterized by bidirectional influences; however, limited information is available regarding the temporal dynamics of these effects. The goal of this investigation was to examine how these psychoimmunological interdependencies unfold over time under conditions of "life as it is lived". For this purpose, three healthy women collected their entire urine over a period of approximately two months at 12-h intervals (8 am-8 pm, 8 pm-8 am), resulting in a total of 112 to 126 consecutive measurements per subject. In addition, among other regular psychological assessments, the subjects completed the EWL-60-S, an emotional state questionnaire, each morning and evening. To assess the extent of T-helper type 1 immune activation, the neopterin per creatinine concentration was measured in the urine samples using high-pressure liquid chromatography. The dynamic relationships between the time series of the six emotional states (performance-related activity, general inactivity, extraversion/introversion, general feeling of comfort, emotional irritation, anxiety/depressiveness) and urinary neopterin levels were estimated in vector-autoregressive models and evaluated using Grangercausality tests, impulse-response functions and forecast error variance decompositions. The findings showed that emotional states explained up to 20% of the variance of urinary neopterin per creatinine levels, whereby most of the effects occurred within a period of approximately three days. Across all subjects, increases in anxiety/depressiveness and extraversion led to increases in neopterin levels, while a general feeling of comfort led to decreases in neopterin. These results emphasize the importance of the interdependencies between emotional states and immune system activity and showcase the potential that intensive longitudinal study designs offer for psychoneuroimmunology.
Created from Fastlane, Scopus look-up

Expression of toll like receptor 8 (TLR8) in specific groups of mouse hippocampal interneurons - Seizer, Lennart; Rahimi, Sadegh; Santos-Sierra, Sandra; Drexel, Meinrad (PLoS ONE, 2022)
Toll-like receptors (TLR) are one of the main constituents of the innate immune system in mammals. They can detect conserved microbial structures (pathogen-associated molecular patterns) and host-derived ligands that are produced during cellular stress and damage (danger-associated molecular patterns) and may then initiate an intracellular signaling cascade leading to the expression of pro-inflammatory cytokines and immediate immune responses. Some TLR (TLR1, 2, 4, 5, and 6) are expressed on the cell surface while others (TLR3, 7, 8 and 9) are present on the surface of endosomes and their ligands require internalization before recognition is possible. Several TLR have also been detected in neurons where they may serve functions that are not related to immune responses. TLR2, 3, and 4 have been described in cortical neurons and, for TLR4, a seizure-promoting role in epilepsies associated with inflammation has been shown. TLR3, 7, and 8 expressed in neurons seem to influence the growth or withdrawal of neurites and robust activation of TLR8 in neurons may even induce neuronal death. The goal of the current study was to investigate the expression of TLR8 in the hippocampus of mice during postnatal development and in adulthood. We focused on three functionally distinct groups of GABAergic interneurons characterized by the expression of the molecular markers parvalbumin, somatostatin, or calretinin, and we applied double fluorescence immunohistochemistry and cell counts to quantify co-expression of TLR8 in the three groups of GABA-interneurons across hippocampal subregions. We found subregion-specific differences in the expression of TLR8 in these interneurons. During postnatal development, TLR8 was detected only in mice older than P5. While only a small fraction of hippocampal calretinin-positive interneurons expressed TLR8, most parvalbumin-positive interneurons in all hippocampal subregions co-expressed TLR8. Somatostatin-positive interneurons co-expressing TLR8 were mainly present in hippocampal sector CA3 but rare in the dentate gyrus and CA1. High expression of TLR8 in parvalbumin-interneurons may contribute to their high vulnerability in human temporal lobe epileps
Keywords: Interneurons; Hippocampus; Toll-like receptors; Neurons; Dentate gyrus; Pyramidal cells; Granule cells; Neuronal dendrites

How stable are psychoneuroimmune effects over time? - Seizer, Lennart; Schubert, Christian (Brain Behavior and Immunity, 2024)
Created from Fastlane, Scopus look-up

Improving mental health by improving the mental health literacy? Study protocol for a randomised controlled evaluation of an e-mental health application as a preventive intervention for adolescents and young adults - Krokos, Olivia; Brandhorst, Isabel; Seizer, Lennart; Gawrilow, Caterina; Löchner, Johanna (Internet Interventions, 2024)
Background: From the age of 14, many adolescents enter a vulnerable developmental phase, with a sharp increase in mental illness at 16. The COVID19 pandemic has further exacerbated this issue. Hence, universal and easily accessible prevention in the young is needed. E-mental health interventions are on the rise due to numerous benefits such as potential low-costs, low-threshold and high scalability. However, effectiveness and acceptance of mobile health (mHealth) preventive interventions remain unresearched. Method: In a two-armed, randomised controlled study design adolescents and young adults from 14 years old will be recruited. Following an initial baseline assessment, they will be randomised to a) the intervention group (IG, n = 75), which will receive a mHealth intervention (the application ‘Mental Health Guide’, co-developed by lived experience experts) or b) the waiting list control group (CG, n = 75). Both groups will be followed up after 3 and 6 months following post assessment. We hypothesize an increase in mental health literacy in the IG compared to the CG for post and follow-up assessment (primary outcome: Mental Health Literacy Scale). In addition, we expect an improvement in mental health and psychological well-being, improved emotion regulation, reduced psychological distress, as well as good quality ratings in usability and acceptance in the use of the ‘Mental Health Guide’ We performed multiple simulations of possible outcome scenarios, incorporating an array of factors, to generate realistic datasets and obtain accurate estimates of statistical power. Conclusion: As a first-of-its-kind in this field, this study investigates whether a mHealth intervention based on mental health literacy may improve the mental health literacy and further aspects of psychological functioning of young people in a vulnerable phase. Furthermore, the results promise to provide important knowledge of how universal prevention may be implemented with low costs for diverse populations. Trial registration: This trial was registered in the DRKS register (DRKS-ID: DRKS00031810) on 23 June 2023.
CRIS-Team Scopus Importer:2024-11-26
Keywords: Adolescence; Mental health literacy; mHealth; Prevention

Large language models for mental health - Triantafyllopoulos, Andreas; Terhorst, Yannik; Tsangko, Iosif; Pokorny, Florian B.; Bartl-Pokorny, Katrin D.; Seizer, Lennart; Seizer, Lennart; Klein, Ayal; Chim, Jenny; Atzil-Slonim, Dana; Liakata, Maria; Buehner, Markus; et al. (2025)
Digital technologies have long been explored as a complement to standard procedure in mental health research and practice, ranging from the management of electronic health records to app-based interventions. The recent emergence of large language models (LLMs), both proprietary and open-source ones, represents a major new opportunity on that front. Yet there is still a divide between the community developing LLMs and the one which may benefit from them, thus hindering the beneficial translation of the technology into clinical use. This divide largely stems from the lack of a common language and understanding regarding the technology's inner workings, capabilities, and risks. Our narrative review attempts to bridge this gap by providing intuitive explanations behind the basic concepts related to contemporary LLM
https://cris.fau.de/converis/publicweb/Publication/336145585

Lessons learned from a multimodal sensor-based eHealth approach for treating pediatric obsessive-compulsive disorder - Klein, Carolin S.; Hollmann, Karsten; Kühnhausen, Jan; Alt, Annika K.; Pascher, Anja; Seizer, Lennart; Primbs, Jonas; Ilg, Winfried; Thierfelder, Annika; Severitt, Björn; Passon, Helene; Wörz, Ursula; et al. (Frontiers in Digital Health, 2024)
Introduction: The present study investigates the feasibility and usability of a sensor-based eHealth treatment in psychotherapy for pediatric obsessive-compulsive disorder (OCD), and explores the promises and pitfalls of this novel approach. With eHealth interventions, therapy can be delivered in a patient's home environment, leading to a more ecologically valid symptom assessment and access to experts even in rural areas. Furthermore, sensors can help indicate a patient's emotional and physical state during treatment. Finally, using sensors during exposure with response prevention (E/RP) can help individualize therapy and prevent avoidance behavior. Methods: In this study, we developed and subsequently evaluated a multimodal sensor-based eHealth intervention during 14 video sessions of cognitive-behavioral therapy (CBT) in 20 patients with OCD aged 12-18. During E/RP, we recorded eye movements and gaze direction via eye trackers, and an ECG chest strap captured heart rate (HR) to identify stress responses. Additionally, motion sensors detected approach and avoidance behavior. Results: The results indicate a promising application of sensor-supported therapy for pediatric OCD, such that the technology was well-accepted by the participants, and the therapeutic relationship was successfully established in the context of internet-based treatment. Patients, their parents, and the therapists all showed high levels of satisfaction with this form of therapy and rated the wearable approach in the home environment as helpful, with fewer OCD symptoms perceived at the end of the treatment. Discussion: The goal of this study was to gain a better understanding of the psychological and physiological processes that occur in pediatric patients during exposure-based online treatment. In addition, 10 key considerations in preparing and conducting sensor-supported CBT for children and adolescents with OCD are explored at the end of the article. This approach has the potential to overcome limitations in eHealth interventions by allowing the real-time transmission of objective data to therapists, once challenges regarding technical support and hardware and software usability are addressed. Clinical Trial Registration: www.ClinicalTrials.gov, identifier (NCT05291611).
CRIS-Team Scopus Importer:2024-11-26
Keywords: children and adolescents; exposure; internet-based cognitive behavioral therapy; obsessive-compulsive disorder; sensor technology; usability

Mixed-methods analysis of sickness behavior during a natural experiment: An integrative single-case study - Schubert, Christian; Seizer, Lennart; Sophia Lauby, Nina Camille; Fuchs, Dietmar (Comprehensive Psychoneuroendocrinology, 2025)
Sickness behavior is a coordinated set of psychological changes mediated by immune system activity, e.g., during infection and wounding. It is an adaptive response to conserve energy and resources in support of immune activity and to protect the community by signaling others that one is ill. In this integrative single-case study, a 27-year-old healthy woman collected her entire urine over a period of 63 days in continuous 12-h intervals (126 measurements in total). In addition, among other regular psychological assessments, she completed an emotional state questionnaire (EWL) each morning and evening, and had an in-depth psychological interview once a week. In the urine samples, neopterin, cortisol, and creatinine were measured. Coincidentally, the subject experienced a period of sickness during the study period, lasting two days (from 12-h interval 21 to 24), accompanied by fatigue, vomiting, diarrhea, low-grade fever, and increases in urinary neopterin and cortisol concentrations. During this sickness period, structural breaks occurred in the time-series of two positive emotional states, i.e., performance-related activity and general feeling of comfort, with significant drops in their mean levels lasting for over 50 days until the end of the study. The intensive longitudinal data set collected in this integrative single-case study makes it possible to adopt a biopsychosocial meta-perspective (bottom-up, top-down) when interpreting the results.
CRIS-Team Scopus Importer:2025-06-06
Keywords: Biopsychosocial; Cortisol; Integrative single-case study; Neopterin; Psychoneuroimmunology; Sickness behavior; Time series

Nonlinear and symptom specific associations between chronotype and depression - Seizer, Lennart; Martínez-Albert, Estefanía; Löchner, Johanna (Scientific Reports, 2024)
The chronotype of individuals has been found to be predictive of depression risk and associated with the severity of depression. However, since depression is a phenotypically heterogeneous disease, it seems improbable that chronotype plays a role in every instance of depression. This study investigates the association between the two, while considering possible symptom-specificity and non-linearity of the relationship, utilizing a large sample from the National Health and Nutrition Examination Survey (N = 5217; 54% female; Age: M = 52.65, SD = 18.76). Depression symptoms were assessed using the Patient Health Questionnaire-9 (PHQ-9), and chronotype was determined by calculating sleep midpoints. Further, we also explored the potential mediating role of systemic inflammation, measured by C-reactive protein (CRP) levels, in the chronotype-depression link. The findings substantiate previous research indicating late chronotypes to be associated with higher PHQ-9 sum scores, with a minimum in PHQ-9 at a sleep midpoint of 02:49. The study further differentiates between individual depression symptoms, uncovering varying patterns of association with chronotype. No significant effect of chronotype on levels of CRP was found, suggesting that the link between chronotype and depression symptoms may not be directly mediated and appears to be stable and independent from systemic inflammation. The study highlights the non-linear and symptom-specific nature of the chronotype-depression connection and suggests the need for further, longitudinal studies to elucidate causal mechanisms and potential mediators.
Created from Fastlane, Scopus look-up
Keywords: Chronotype; Depression; Inflammation; Sleep; Symptom

On the Role of Psychoneuroimmunology in Oral Medicine - Seizer, Lennart; Schubert, Christian (International Dental Journal, 2022)
Psychoneuroimmunology (PNI) is an area of interdisciplinary research exploring the complex interactions within the immuno-neuro-endocrine system in response to psychosocial influences. Such influences can trigger neurological changes, leading to immunological effects related to the emergence and course of various diseases. This concise clinical review explores the role of PNI in oral medicine in three exemplary models of oral disease: periodontitis, herpes labialis, and oral lichen planus. Previous literature has shown that psychosocial stress is related to exacerbations in these three oral diseases and to poorer overall oral health. The presumed biological mechanisms affect the activity of stress axes, i.e. the hypothalamus-pituitary-adrenal (HPA) axis and the sympathetic nervous system (SNS), and subsequent immune system dysregulation. Although these PNI mechanisms remain poorly understood, several stress reduction interventions in clinical oral medicine have already yielded promising results. In future work, the elucidation of pathways within PNI networks will require carefully designed studies with sensitive methodology, e.g. the integrative single-case design. A biopsychosocial approach has the potential to move disease models in oral medicine from simple connections rooted in empirical dualism and reductionism to the establishment of network-based models. Further research on these complex connections should lead to novel clinical approaches and preventive strategies in oral medicine.
Created from Fastlane, Scopus look-up
Keywords: Herpes labialis; Integrative single-case study; Oral lichen planus; Periodontitis; Psychoneuroendocrinology; Psychoneuroimmunology

Personalized therapy in rheumatoid arthritis (PETRA): a protocol for a randomized controlled trial to test the effect of a psychological intervention in rheumatoid arthritis - Seizer, Lennart; Huber, Ellis, Miriam Schirmer; Hilbert, Sven; Wiest, Eva Maria; Schubert, Christian (Trials, 2023)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that primarily affects cartilage and bone. Psychological stress can both trigger disease exacerbation and result from disease activity. As standard pharmacological interventions alone have limited success in treating RA, a more comprehensive biopsychosocial approach to treatment has been recommended. In this prospective randomized controlled trial (RCT), a psychotherapeutically guided, group-based intervention program will be conducted with RA patients over a period of 9 months. This program combines a dynamic-interactional model with disorder-specific coping-oriented perspectives to improve patients’ social, emotional, and problem-solving competencies as well as stress system functional status. The enrolment of 440 patients, randomly allocated to either an intervention (n = 220) or control group (n = 220), is planned. To evaluate the intervention effect, various indicators of RA disease activity, stress system activity, and psychological condition will be assessed through sets of standardized questionnaires and biochemical analyses of blood and saliva samples. Moreover, healthcare-related costs for each patient will be obtained using routine health insurance data. Outcome variables will be measured in all patients at regular intervals prior to intervention (baseline), during the 9-month intervention (five time points), and during a 9-month follow-up phase (three time points), allowing the comprehensive analysis of within- and between-subject effects, i.e. trajectories of the target variables in the intervention and control groups. In addition, to investigate the intervention effects on real-life stress system functioning in RA, 10 integrative single-case studies (n = 5 from the intervention group, n = 5 from the control group) will be conducted. In each study, once before and after the 9-month intervention, urine samples will be collected, and patients will fill out questionnaires for approximately 1 month at 12-h intervals. Moreover, weekly in-depth interviews will be conducted with patients to determine their previous week’s emotionally positive and negative incidents. Using time series analysis, it is then possible to investigate whether and how stress system function in these RA patients has improved from the applied intervention. By using both an investigational macro- and microperspective, this project aims to evaluate a psychological intervention in the routine care of individuals with RA. Trial registration German Clinical Trials Register DRKS00028144. Registered on 1 March 2022.
Created from Fastlane, Scopus look-up
Keywords: Group-based intervention; Integrative single-case study; Psychoneuroimmunology; Randomized controlled trial; Rheumatoid arthritis

Psychotherapy 2.0 - Application context and effectiveness of sensor technology in psychotherapy with children and adolescents: A systematic review - Alt, Annika K.; Pascher, Anja; Seizer, Lennart; von Fraunberg, Marlene; Conzelmann, Annette; Renner, Tobias J. (Internet Interventions, 2024)
Background: E-mental health applications have been increasingly used in the psychotherapeutic care of patients for several years. State-of-the-art sensor technology could be used to determine digital biomarkers for the diagnosis of mental disorders. Furthermore, by integrating sensors into treatment, relevant contextual information (e.g. field of gaze, stress levels) could be made transparent and improve the treatment of people with mental disorders. An overview of studies on this approach would be useful to provide information about the current status quo. Methods: A systematic review of the use of sensor technology in psychotherapy for children and adolescents was conducted with the aim of investigating the use and effectiveness of sensory technology in psychotherapy treatment. Five databases were searched for studies ranging from 2000 to 2023. The study was registered by PROSPERO (CRD42023374219), conducted according to Cochrane recommendations and used the PRISMA reporting guideline. Results: Of the 38.560 hits in the search, only 10 publications met the inclusion criteria, including 3 RCTs and 7 pilot studies with a total of 257 subjects. The study population consisted of children and adolescents aged 6 to 19 years with mental disorders such as OCD, anxiety disorders, PTSD, anorexia nervosa and autistic behavior. The psychotherapy methods investigated were mostly cognitive behavioral therapy (face-to-face contact) with the treatment method of exposure for various disorders. In most cases, ECG, EDA, eye-tracking and movement sensors were used to measure vital parameters. The heterogeneous studies illustrate a variety of potential useful applications of sensor technology in psychotherapy for adolescents. In some studies, the sensors are implemented in a feasible approach to treatment. Conclusion: Sensors might enrich psychotherapy in different application contexts. However, so far there is still a lack of further randomized controlled clinical studies that provide reliable findings on the effectiveness of sensory therapy in psychotherapy for children and adolescents. This could stimulate the embedding of such technologies into psychotherapeutic process. https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023374219, identifier [CRD42023374219].
Created from Fastlane, Scopus look-up

Real-Life Cause-Effect Relations Between Urinary IL-6 Levels and Specific and Nonspecific Symptoms in a Patient With Mild SLE Disease Activity - Schubert, Christian; Seizer, Lennart; Chamson, Emil; König, Paul; Sepp, Norbert; Ocaña-Peinado, Francisco M.; Schnapka-Köpf, Mirjam; Fuchs, Dietmar (Frontiers in Immunology, 2021)
Background: Little is known about the real-time cause-effect relations between IL-6 concentrations and SLE symptoms. Methods: A 52-year-old woman with mild SLE activity collected her entire urine for the determination of IL-6/creatinine and protein/creatinine levels (ELISA, HPLC) for a period of 56 days in 12 h intervals (total: 112 measurements). Additionally, she answered questionnaires (VAS) on oral ulceration, facial rash, joint pain, fatigue and tiredness and measured her temperature orally twice a day. Time-series analyses consisted of ARIMA modeling and cross-correlational analyses (one lag = 12 h, significance level = p < 0.05). Results: Statistical analyses showed that increased urinary IL-6 concentrations preceded increased urinary protein levels by 36–48 h (lag3: r=+.225; p=.017) and that, in the opposite direction of effect, increased urinary protein preceded urinary IL-6 decreases by 12–24 h (lag1: r=–.322; p<.001). Moreover, urinary IL-6 increases co-occurred with increased oral ulceration (lag0: r=+.186; p=.049); after 48–60 h, however, IL-6 increases showed a strong tendency to precede oral ulceration decreases (lag4: r=–.170; p=.072). Increases in facial rash preceded decreases in urinary IL-6 after 84–96 h (lag7: r=–.215; p=.023). As to fatigue, increases in urinary IL-6 co-occurred with decreased fatigue (lag0: r=–.193; p=.042); after 84–96 h, however, IL-6 increases preceded fatigue increases (+lag7: r=+.189; p=.046). Finally, joint pain, tiredness and body temperature did not significantly correlate with urinary IL-6 concentrations in either direction of effect. Conclusions: The results of this evaluation point to real-life feedback mechanisms between immune activity and SLE symptoms. Comparison with a previous evaluation of this patient suggests a counterregulatory mechanism between Th1 activity and IL-6. These findings are preliminary and require replication to draw firm conclusions about the real-time relation between IL-6 and SLE disease activit

The influence of everyday emotions on mucosal immunity: An intensive longitudinal modeling approach - Seizer, Lennart; Löchner, Johanna (Psychophysiology, 2024)
Mucosal immunity is a multifaceted system of immunological responses that provides a barrier against pathogenic invasion and can be regulated by psychosocial and neuroendocrine factors. The present study aims to elucidate the association between everyday emotional states, emotion regulation skills, and mucosal immunity by utilizing an ambulatory assessment approach. 30 healthy subjects (61% male; M = 30.18 years old) completed an emotion questionnaire (PANAS) and collected saliva samples via passive drool to determine salivary immunoglobulin-A (S-IgA) excretion rate three times a day over a period of 1 week. In a multi-level model, the influence of emotions on S-IgA, both on a within-subject and between-subject level, was estimated. We found that most of the variation in S-IgA (74%) was accounted for by within-subject changes rather than stable between-subject differences. On a within-subject level, negative emotions had a significant positive effect on S-IgA levels (b = 1.87, p =.015), while positive emotions had no effect. This effect of negative emotions was moderated by the individual emotion regulation skills, with higher regulation skills corresponding to smaller effects (b = −2.67, p =.046). Furthermore, S-IgA levels decreased over the course of a day, indicating circadian rhythmicity (b = −0.13, p =.034). These results highlight the possibilities of intensive longitudinal data to investigate the covariance between psychological and immunological states over time.
CRIS-Team Scopus Importer:2024-11-26
Keywords: ambulatory assessment; ecological momentary assessment; emotion; immunoglobulin; intensive longitudinal data; psychoneuroimmunology

Timing matters: A meta-analysis on the dynamic effect of stress on salivary immunoglobulin - Seizer, Lennart; Stasielowicz, Lukasz; Löchner, Johanna (Brain Behavior and Immunity, 2024)
The impact of psychological stress on physiological systems has been a focus of extensive research, particularly in understanding its diverse effects on immune system activity and disease risk. This meta-analysis explores the dynamic effect of acute stress on salivary immunoglobulin-A (S-IgA) levels, a key biomarker for secretory immunity within the oral environment. Analyzing data from 34 samples comprising 87 effect sizes and a total of 1,025 subjects, a multi-level approach is employed to account for the temporal variability in measuring the stress response. The results reveal a significant increase in S-IgA levels peaking around 10 min after stress exposure, followed by a return to baseline levels approximately 30 min later. In addition, the meta-analysis identified several research gaps of the extant literature, such as limitations in the considered time lag after stress. In conclusion, the findings emphasize the temporal nuances of the S-IgA response to stress, which can help to infer potential biological pathways and guide sampling designs in future studies. Further, we highlight the use of a multi-level meta-analysis approach to investigate the temporal dependencies of the interplay between stress and immune functioning.
CRIS-Team Scopus Importer:2024-11-26
Keywords: Adaptive immunity; B-cell; Psychoneuroimmunology; Saliva; Stress

Tracking health-related quality of life dynamics: Advances in ambulatory assessment methods - Löchner, Johanna; Moshe, Isaac; Schiepek, Günter; Schuller, Björn; Schoedel, Ramona; Rodgar, Majid; Wac, Katarzyna; Seizer, Lennart (Brain Behavior and Immunity Integrative, 2024)
Assessing quality of life in clinical practice and research via patient-reported outcomes is an emerging practice enabling the assessment of individual well-being across different populations and conditions, such as immune-mediated and inflammatory disorders. Standardized questionnaires have traditionally been used for this purpose, but they have several limitations inherent to one-time snapshots from recall-based self-reports. Ambulatory measures may provide an alternative approach to assessing quality of life that allows capturing an individual’s states and behaviours in the context of daily life. In this overview article, we define ambulatory measures, including ecological momentary self-reports, wearable sensors, biochemical sampling, and smartphone sensing, that may be used to estimate quality of life, and present examples of studies that have used these measures. Additionally, we highlight the benefits of integrating multi-method ambulatory measures and overview methods for combining and analyzing them, including data fusion techniques and machine learning. While there are still challenges and limitations to overcome, the integration and application of ambulatory measures in medical research and clinical practice have the potential to provide a more comprehensive and accurate assessment of the quality of (everyday) lif